A relação entre moralidade e legalidade na compreensão do progresso moral em Kant - Poersch, Claiton Derli Seibert (2020)
Immanuel Kant’s moral proposal is a cause of dazzle and divergences, either because of his strict character, or by the breadth that allows him to impute. In view of this scenario, with a view to responding to an academic restlessness arising from the realized studies, both in philosophy and in law, allied to a search for a deepening in the philosophical theory of the author regarding the moral, the present dissertation has as theme the analysis of the Civil Law and the Moral Law in Kant’s theory and the implication of both in the construction of moral progress, seeking to answer the questioning: “what is the relation between moral duty and legal duty in the proposal to build the moral progress of Immanuel Kant?’’. The general objective seeks the investigation of the elements linked to the moral and legal duties inserted in the theory of the alluded philosopher starting from the analysis of the insert elements, especially in The Foundation of the Metaphysics of Customs and Metaphysics of Customs with a view to establish the theoretical bases from which the philosopher comes to the ultimate analysis of moral progress. Therefore, an itinerary will follow, beginning by rebuilding the concepts of goodwill, duty, moral and categorical imperative, moral and maximum law, autonomy and freedom, evidencing their relevance to Kant’s propositions regarding the construction of legal and moral principles. Continuous act, the objective is to present the distinction between the modus operandi of moral precept and civil legislation, explaining that in the first the founding principle is internal coercion whose target is autonomy, while in the second external coercion is exercised, characterizing the heteronymous act. Finally, based on the analyses until then, it is intended to demonstrate how Kant builds his theory in order to allow the existence notion of moral progress and its implications for the relations established between morality and legality. The discussions proposed here are current, applying to the socio-political-economic reality, especially regarding the moral and legal principles and their influence on the construction of a Kingdom of Ends.